Design Criteria of an Activated Carbon Bed for Dechlorination of Water - Y. Abdul – Ahad, Muna (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Granular carbon can be used after conventional filtration of suspended matter or, as a combination of filtration - adsorption medium. The choice of equipment depends on the severity of the organic removal problem, the availability of existing equipment, and the desired improvement of adsorption condition.Design calculations on dechlorination by granular - carbon filters considering the effects of flow rate, pH , contact time, head loss and bed expansion in backwashing , particle size, and physical characteristics were considered assuming the absence of bacteria or any organic interface .